Sectoral Vulnerabilities and Labor Transitions in Urban Areas During the COVID-19 Pandemic and Recovery - Anggara, Rizki Tri; Alfahma, Elsya Gumayanti (Jurnal Ilmu Ekonomi Terapan, 2025)
Objective: This study analyzes employment transitions in Indonesia's urban labor markets during the COVID-19 pandemic and recovery period (2020–2022). It empirically examines shifts between formal employment, informal employment, and unemployment, focusing on resilience and inclusivity in the labor market. Design/Methods/Approach: Using multinomial logistic regression on data from Indonesia's National Labor Force Survey (SAKERNAS) from 2020–2022, the study examines socio-demographic and sectoral factors associated with employment transitions. Findings: The results show significant socio-demographic and sectoral disparities in employment transitions. Workers in the manufacturing sector face the highest risks of transitioning to informal employment or unemployment, while the services sector demonstrates greater resilience. Digital access and higher education serve as protective factors, though skill mismatches may persist among tertiary-educated workers. Women and younger workers remain disproportionately vulnerable to unemployment. Originality/Value: This study fills a gap by centering urban labor markets in Indonesia during the COVID-19 shock and early recovery (2020–2022)—a context underexplored in prior work. It jointly models transition among formal employment, informal employment, and unemployment. The analysis integrates digital access alongside socio-demographic and sectoral affiliations, revealing urban-specific mechanisms—heightened job competition and dependence on volatile services/manufacturing—that existing literature often overlooks. Practical/Policy implication: The findings highlight the need for targeted policy interventions to strengthen labor market resilience and inclusivity during economic disruptions. Recommendations include expanding digital infrastructure and literacy, aligning vocational training with market demands, and implementing sector-specific measures such as enhancing labor protections in manufacturing and extending social protections for informal workers in the primary sector.